Atrazine sensitivity varies among soybean cultivars - Shwetha S. Ramanathan; Travis W. Gannon; Wesley J. Everman; Anna M. Locke (Agrosystems, Geosciences & Environment)
Abstract Atrazine carryover from application to a monocot crop may adversely affect soybean (Glycine max (L.) Merr.) grown in rotation. Here, we tested the hypothesis that genotype selection could reduce atrazine carryover damage to soybean. Five commercially relevant soybean varieties were evaluated for differences in sensitivity to a range of atrazine rates using visual ratings, photosynthetic, and biomass parameters. Visual injury ratings and photosynthetic gas exchange, chlorophyll fluorescence, relative chlorophyll content (SPAD), and aboveground biomass were measured during vegetative stages. Under 9.0 g a.i. ha−1 atrazine, SH 5515 LL exhibited visual injury and aboveground fresh biomass reduction but was unaffected in net photosynthesis rate (A) and effective quantum yield of photosystem II (ϕPSII) compared to controls. By 21 days after emergence (DAE), P53A67X recovered in A and ϕPSII, and AG56X8 recovered in SPAD. S52RS86 remained unaffected visually and photosynthetically at this atrazine rate. All genotypes treated with 179.2 g a.i. ha−1 atrazine showed higher injury ratings and lower SPAD, A, and ϕPSII after 7 DAE and lower aboveground biomass 21 DAE except S52RS86, which was similar in SPAD throughout. Atrazine at 358.4 and 716.8 g a.i. ha−1 caused plant death in all genotypes 14 DAE. Visual ratings were strongly correlated with photosynthetic measurements and aboveground biomass at each sampling. Soybean atrazine sensitivity is a function of atrazine concentration in the soil and genotype‐specific tolerance or recovery ability, indicating that growers can select soybean genotypes that reduce risk when atrazine carryover is suspected.